2016
DOI: 10.1002/adom.201600229
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocene‐Grafted Photochromic Triads Based on a Sterically Hindered Ethene Bridge: Redox‐Switchable Fluorescence and Gated Photochromism

Abstract: Multifunctional switches, as well as gated photochromism, are particularly challenging. Here, a ferrocene (Fc)‐modified photochromic diarylethene (DAE) with sterically hindered ethene bridge, in which the photo‐inactive parallel conformer and photoactive antiparallel conformer are individually investigated, is reported. The photoswitchable triad system (parallel conformer p‐Fc and anti‐parallel ap‐Fc) contains three functional parts: photochromic DAE unit, naphthalimide chromophore, and redox‐active ferrocene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Upon increasing the proportion of the oxidizing agent, the signals of methylene moiety were shifted downfield and finally, they totally vanished indicating the complete oxidation. The disappeared resonances gradually recovered upon addition of reducing agent showing the reversible redox behavior . The use of diarylethene is limited due to the problem of oxidation which renders the entire sequence irreversible.…”
Section: Ferrocene‐based Electro and Photo Responsive Materialsmentioning
confidence: 91%
See 4 more Smart Citations
“…Upon increasing the proportion of the oxidizing agent, the signals of methylene moiety were shifted downfield and finally, they totally vanished indicating the complete oxidation. The disappeared resonances gradually recovered upon addition of reducing agent showing the reversible redox behavior . The use of diarylethene is limited due to the problem of oxidation which renders the entire sequence irreversible.…”
Section: Ferrocene‐based Electro and Photo Responsive Materialsmentioning
confidence: 91%
“…Cai et al . synthesized some photoinduced electron transfer (PET) generators having diarylethene (DAE) as a photoswitchable unit and ferrocene‐based naphthalimide . It was found that ferrocene grafted triads can give electro and photoresponsive properties by changing the source of light or redox cycle (Figure ) .…”
Section: Ferrocene‐based Electro and Photo Responsive Materialsmentioning
confidence: 99%
See 3 more Smart Citations